The Graphical Representation of The Cell Count in The Aspirate as A Groundbreaking Method for The Diagnosis of A Painful Hip Endoprosthesis - Hoyka, Marius; Weissbarth, Elke; Berger, Irina; Fink, Bernd (Archives of Clinical and Medical Case Reports, 2025)
Following total hip arthroplasty, pain can occur for a variety of reasons even if the patient has experienced years free of any discomfort. The cause of this pain is often difficult to identify. In the following, a case is described in which the diagnosis of trunnionosis could be made using a new method of graphic visualisation of cell count analysis of an aspirate and the otherwise misinterpretation of a periprosthetic infection with its therapy-related consequences could be avoided.